Experimental investigation on the bearing mechanism of Perfobond rib shear connectors. (15th March 2018) - Zhao, Canhui; Li, Zhixiang; Deng, Kailai; Wang, Weian
Highlights: Tests on 18 high confined PBLs were performed to obtain the bearing mechanism. Influences of four design parameters were quantitatively investigated. The proposed ultimate bearing capacity formula presented satisfactory accuracy. Contributions from the shear-friction force and dowel action were quantified. Abstract: The bearing capacity of Perfobond rib shear connectors (PBL shear connectors) mainly comes from adhesion, interfacial frictional force, dowel actions, and end bearing force. However, the contribution of each component to the total bearing capacity has not been deeply addressed. An experimental study on 18 PBL shear connectors deeply embedded in massive reinforced concrete was performed to determine the bearing mechanism. The strain distributions were sophisticatedly measured by the optical fibers on the perforate steel plate and passing rebar. Results showed that key design parameters such as diameter of the holes in the perforated steel plate, diameter of passing rebar and the transverse reinforcement ratio influenced the bearing capacity. A formula was proposed for estimating the bearing capacity of PBL shear connectors, which quantifies the portions of shear-friction force and the dowel action of the passing rebar. Comparisons between the analytical solution and test results validated the proposed formula. With this validated formula, further dissection of the bearing mechanism of PBL shear connectors was carried out.